2015
DOI: 10.1016/j.fertnstert.2014.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of preimplantation genetic diagnosis in neurofibromatosis type 1

Abstract: Capsule: In a retrospective study of patients with neurofibromatosis 1 undergoing PGD, only 37% of all biopsied embryos were confirmed to be unaffected by NF1 and at least 27% of couples achieved a live birth. Conclusion:Advances in biopsy and diagnostic techniques which increase the number of unaffected embryos may improve live birth rates for patients with NF1. Clinicians should counsel patients about their fertility and reproductive options early, using diseasespecific data to set appropriate expectations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 24 publications
0
11
1
Order By: Relevance
“…The present prospective cohort study from an inner‐city tertiary PGD referral centre in London showed that for couples at risk of having an offspring affected with SCD, the live‐birth rate for PGD per couple embarking on PGD treatment was 63% after a mean of 1·2 fresh PGD cycles started. These figures are significantly higher than previous reports over the last two decades, in which the live‐birth rate following PGD ranged between 13% and 53% 18–21 . Furthermore, recently published data from the European Society of Human Reproduction and Embryology (ESHRE) PGD Consortium 22 reported a clinical pregnancy rate of 31% per embryo transfer, compared to 55% clinical pregnancy rate per embryo transfer in our present study.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…The present prospective cohort study from an inner‐city tertiary PGD referral centre in London showed that for couples at risk of having an offspring affected with SCD, the live‐birth rate for PGD per couple embarking on PGD treatment was 63% after a mean of 1·2 fresh PGD cycles started. These figures are significantly higher than previous reports over the last two decades, in which the live‐birth rate following PGD ranged between 13% and 53% 18–21 . Furthermore, recently published data from the European Society of Human Reproduction and Embryology (ESHRE) PGD Consortium 22 reported a clinical pregnancy rate of 31% per embryo transfer, compared to 55% clinical pregnancy rate per embryo transfer in our present study.…”
Section: Discussioncontrasting
confidence: 82%
“…These figures are significantly higher than previous reports over the last two decades, in which the live-birth rate following PGD ranged between 13% and 53%. [18][19][20][21] Furthermore, recently published data from the European Society of Human Reproduction and Embryology (ESHRE) PGD Consortium 22 reported a clinical pregnancy rate of 31% per embryo transfer, compared to 55% clinical pregnancy rate per embryo transfer in our present study. The embryo-implantation rate was also higher in our present study compared to the study of De Rycke et al 22 (50% vs. 23%).…”
Section: Discussionmentioning
confidence: 47%
“…81 A study of 156 cycles of preimplantation genetic diagnosis (PGD) in couples with NF1 showed a lower proportion resulting in live birth (versus non-NF1 couples), but the rate was comparable with that seen in couples with other autosomal dominant or X-linked disorders. 116 Prenatal diagnosis is possible through fetal DNA sequencing (obtained via amniocentesis or chorionic villus sampling) of known disease-causing NF1 mutations. 117 Prenatal ultrasound diagnosis of NF1 has been reported, but would be feasible only in the setting of an NF-related lesion that is visible by ultrasound, which accounts for only a small proportion of cases.…”
Section: Contraception Pregnancy and Assisted Fertilitymentioning
confidence: 99%
“…The present case did not have any other features of NF 1. 22 Indications for surgical removal of neurofibromas include cosmetic disfigurement or compression effects.The indication in this case was both for cosmetic disfigurement and improvement in hearing.…”
Section: Discussionmentioning
confidence: 99%